The HIV-1 glycoprotein gp120 elevates NF-kB levels in human cardiomyocytes which may be reversed with the treatment of a sesquiterpene lactone isolated from Vernonia staehelinoides - Coopusamy, Dayaneethie (My University, 2010)
Twenty five years of studying HIV-1 structure and replication have improved diagnosis and treatment of individuals infected with the virus. In particular, the introduction of highly active antiretroviral therapy (HAART) has significantly altered the course of HIV-1 infection by increasing life expectancy and reducing opportunistic infections. However, chronic cardiovascular complications such as HIV associated cardiomyopathy (HIVCM), which manifest later during the course of HIV- 1 infection, have become increasingly evident. Despite its growing incidence, with high cardiovascular morbidity and mortality in young and middle-aged adults, the molecular mechanisms of HIVCM remain poorly understood. A number of pathways have been implicated in HIVCM, including damage initiated by HIV-1 surface glycoprotein, gp120, and dysregulation of NF-κB. NF-κB is a universal transcription factor and it regulates a number of genes, many of which are involved in inflammation, injury and stress response. The ability of HIV-1 to manipulate host signalling pathways, including elevated NF-κB levels, has resulted in efficient viral replication and gene expression. The elevation of NF-κB has also been shown to be involved in animal models of HIVCM but very little work has been conducted on human cells. For this reason, the primary objectives of this thesis were to establish the level of NF-κB in a cellular model of HIVCM by challenging human cardiomyocytes with HIV-1 or gp120 and to mitigate the effect on NF-κB using natural compounds derived from South African indigenous plants. The effect of gp120 and HIV-1 on NF- κB levels in human cardiomyocytes was tested by an ELISA-based assay and immunocytochemistry. This was to determine whether the damage induced by HIV-1 and gp120 is mediated by NF-κB. The results shows that gp120 significantly increased NF-κB levels in human cardiomyocytes compared to control unstimulated cardiomyocytes (p<0.001). One plant compound, the sesquiterpene lactone 106A, significantly reduced the NF-κB response by human cardiomyocytes to gp120 stimulation (p<0.05). Taken together, this study suggests that the activation of NF-κB by gp120 has a role to play in a cellular model of HIVCM and that the sesquiterpene lactone 106A could prove valuable in further studies on the modulation of cellular responses due to gp120 and HIV-1 induced stress in human cardiomyocytes